Determination of the local site occupancy of Eu3+ ions in ZnAl2O4 nanocrystalline powders - Silva, da [UNESP]; Abreu, Alison [UNESP]; Davolos, Marian Rosaly [UNESP]; Rosaly, Marian [UNESP] (Elsevier B.V., 2011)
Once lanthanides-doped ZnAl2O4 have attracted attention for highly efficient phosphors and due to the complexity of this system, this work is focused in the understanding of the local site occupancy of the doped ions in the spinet structure by using Eu3+ as a spectroscopic probe. Europium(III)-doped ZnAl2O4 nanocrystalline powder samples were prepared by the Pechini method. Different heat treatment temperatures and doping levels were investigated. No impurities of residual Eu2O3 were observed for the samples with Eu3+ doping levels up to 10 at.%, indicating that the doping ions are diluted into the host. The luminescence spectroscopy from the Eu3+ ions revealed the Eu3+ ions might occupy at least two non-centro-symmetric sites and that the occupation ratio might be dependent on the heat treatment or doping level. It is observed that one site is related to a high covalent environment while at the other the ionic character prevails. This behavior is in agreement with the luminescence lifetime results. The decay curves were fitted according to double first-order decay model and it was confirmed the covalence difference between the two sites and also the population variation with the doping level. There are strong evidences that the europium ions substitute for the aluminum ones in the normal spinel structure. It cannot be disregarded that the dopant ions may be present on the surface of the particles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Spinel structure; Phosphors; Spectroscopic probes